Efektivitas Konseling Kelompok Realita untuk Meningkatkan Motivasi Belajar Siswa SMP di Desa Siman Kecamatan Kepung Kabupaten Kediri - Ligasari, Otista Nima; Navion, Febranti Putri (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2021)
This study aims to determine the effectiveness of reality group counseling to increase the learning motivation of junior high school students in Siman Village. In this study, researchers used a quantitative approach to this type of experiment. Samples were determined using purposive sampling techniques online via a google form. The data analysis techniques used were validity, reliability, normality, and hypothesis testing. The results showed that 1) the Sig. (2-tailed) 0.000 <0.05 indicates that there is a difference in the initial variable with the final variable, 2) the application of reality group counseling can increase the learning motivation of students of class VIII and VIII SMP in Pluncing Hamlet, and 3) the criteria for increasing student learning motivation are in the high category so that reality group counseling is effective at increasing student learning motivation.